2012
DOI: 10.1186/1423-0127-19-102
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-regulated target genes implicated in tumor metastasis

Abstract: Hypoxia is an important microenvironmental factor that induces cancer metastasis. Hypoxia/hypoxia-inducible factor-1α (HIF-1α) regulates many important steps of the metastatic processes, especially epithelial-mesenchymal transition (EMT) that is one of the crucial mechanisms to cause early stage of tumor metastasis. To have a better understanding of the mechanism of hypoxia-regulated metastasis, various hypoxia/HIF-1α-regulated target genes are categorized into different classes including transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
139
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 78 publications
5
139
0
Order By: Relevance
“…Other genes/pathways implicated in this hypoxic response include nuclear factor k B, activator protein-1, mammalian target of rapamycin kinase and the unfolded protein response. [59][60][61] Although these genes/pathways are activated independently, indicating redundancy in oxygen-sensitive pathways, there is also evidence that they can respond to hypoxia in an integrated manner. 62 Early studies have shown that hypoxia selected for cells with defects in apoptosis.…”
Section: Variability In Tumour Oxygenationmentioning
confidence: 99%
“…Other genes/pathways implicated in this hypoxic response include nuclear factor k B, activator protein-1, mammalian target of rapamycin kinase and the unfolded protein response. [59][60][61] Although these genes/pathways are activated independently, indicating redundancy in oxygen-sensitive pathways, there is also evidence that they can respond to hypoxia in an integrated manner. 62 Early studies have shown that hypoxia selected for cells with defects in apoptosis.…”
Section: Variability In Tumour Oxygenationmentioning
confidence: 99%
“…They positively regulate the expression levels of >100 target genes, which encode protein products involved in the response to hypoxia (3)(4)(5). Tumor hypoxia was first described in the 1950s and currently there is increasing evidence to demonstrate that hypoxia is regulated by HIFs and is a common feature in several types of cancer (6)(7)(8)(9). In 1992, Semenza et al (10) identified a nuclear factor, which binds to the 3'-flanking sequence of the human erythropoietin gene (EPO) and promotes the expression of EPO under anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11]14 To survive in hypoxia, cells activate adaptive responses, including gene regulation by hypoxia-inducible factors (HIF)-1alpha (HIF-1α) and -2alpha (HIF-2α). 15,16 Hypoxia allows HIF to escape from normoxia-mediated degradation in the cytoplasm and to translocate into nuclei where they bind to hypoxia-response elements within the regulatory regions of target genes [17][18][19][20] and microRNA. 21,22 The use of HIF inhibitors represents a new strategy for the development of therapies targeting the hypoxic cancer microenvironment.…”
Section: Introductionmentioning
confidence: 99%